Perbedaan Pengetahuan, Sikap, Dan Praktek Keselamatan Dan Kesehatan Kerja Pada Dua Kelompok Tenaga Kerja Wanita Pemecah Batu Di Kota Semarang - Istiarti, Tinuk; Suwondo, Ari; Anureksi, Sri (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2006)
Background : Seventy to eighty percent of workers are working in informal sectors and are not yet covered by the occupational health and safety program. In Central Java, most of the stone breakers are female, who are not insured by the safety program. The general purpose of this research was to know the difference in knowledge, attitude, and behavior oftwo groups of female stone breakers. One of was guided and supervised by public health centers officers, while the other was not.Method : This research uses analytical descriptive survey method by cross sectional design to describe how the respondents implemented occupational health and savety program. For some facotors needed, the data were quantitatively and qualitatively collected. The data were collected through the results of structured interviews with the respondents. Female stone breakers residing in Kecamatan Rowosari Kota Semarang.Thirty female stone breakers of the population were taken as a sample of stone breakers guided and supervised by the public health center officers, while the control group consists of 30 female stone breakers who were not guided and supervised â€œIndependent t testâ€ and â€œlogistic regressionâ€ were used to analyze and statistically test the data.Result : The results of the research indicate the difference in knowledge, attitude, and behavior between the two groups of female stone breakers. From the statistical independent t test, there was a significant difference in knowledge, attitude, and behavior between the two groups (p=0,00<0,05). The results of statistical bivariat logistic regression show the influence of age, education, and wages to guidance of K3 programs. And the multivariate statistical logistic regression show that wages were the most influence.Keywords : knowledge, attitude, behavior, accupational health & safety, female workers.